Technical and economic viability of co-inoculation with Azospirillum brasilense in soybean cultivars in the Cerrado - Galindo, Fernando S. [UNESP]; Teixeira Filho, Marcelo C. M. [UNESP]; Buzetti, Salatier [UNESP]; Ludkiewicz, Mariana G. Z. [UNESP]; Rosa, Poliana A. L. [UNESP]; Tritapepe, Caio A. [UNESP] (Univ Federal Campina Grande, 2018)
Biological nitrogen fixation (BNF) efficiency can be increased by co-inoculation with bradyrhizobia and Azospirillum brasilense, allowing even greater uptake of water and nutrients, leading to higher yields. Thus, this study aimed to evaluate the technical and economic viability of soybean in the Cerrado, according to the cultivars and co-inoculation with Azospirillum brasilense. The experiment was conducted in Selviria, MS, in no-tillage system, in Oxisol, arranged in a randomized block design in a 2 x 2 factorial scheme with two cultivars ('Potencia' and 'Valiosa'), with and without co-inoculation with Azospirillum brasilense in the seed. Co-inoculation with A. brasilense increases grain yield in the cultivars 'Potencia' and 'Valiosa', being economically viable. However, using the cultivar 'Potencia' co-inoculated led to the highest profitability.
Keywords: biological nitrogen fixation; total operating cost; Glycine max; technical performance; economic performance